WATER SOURCE AS THE MAIN RISK FACTOR OF SOIL-TRANSMITTED HELMINTHS INFECTION ON PRIMARY SCHOOL STUDENTS IN ANTIGA VILLAGE, BALI - RONALD SUGIANTO; VANIA SUKARNO; MADE SUDARMAJA I; KADEK SWASTIKA I (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study aims to find out the main risk factor of soil-transmitted helminths (STH) infection, so the results of this study can be used to determine the right steps in STH education and eradication. Methods: This study uses a cross-sectional analytic design. The sample consists of 105 primary school students at “Sekolah Dasar Negeri (SDN) 3” Antiga Village, Bali, using total sampling techniques. To collect data, modified Kato-Katz technique and questionnaire are used. The data then analyzed using logistic regression in the Statistical Package for the Social Sciences version 23 software. Results: The prevalence of STH infection in “SDN 3” Antiga is 14.3%. Three students infected by Ascaris lumbricoides (20%), eight students infected by Trichuris trichiura (53.3%), and four students infected by mix infections (26.7%). The main risk factor of STH infection is the water source from a river (P = 0.001; odds ratio [OR] = 7.875; 95% confidence interval [CI] 2.311–26.836). Conclusion: Of 105 participants, 15 students (14.3%) had STH infection. The highest prevalence of helminths egg found was Trichuris trichiura. The main risk factor of STH infection in this study is the source of water, which is from a river nearby (P = 0.001, OR 7.875, CI 95% 2.311–26.836).